The physiological function and pathological significance of transient receptor potential ankyrin 1 channels in the cerebral artery endothelium - Sullivan, Michelle Nicole, author; Earley, Scott, advisor; Feng, Yumei, advisor; Dinenno, Frank, committee member; Tjalkens, Ronald, committee member; Amberg, Gregory, committee member (Colorado State University. Libraries, 2015)
Endothelial cell Ca2+ dynamics have a significant influence on cerebrovascular tone. Several transient receptor potential (TRP) channels have been shown to mediate Ca2+ influx in the endothelium, including TRP vanilloid 4 (TRPV4), TRPV3, and TRP ankyrin 1 (TRPA1), which activates endothelium-dependent vasodilatory pathways. High resolution Ca2+ techniques have allowed for the recording of unitary TRP channel Ca2+ influx events, called TRP sparklets, in endothelial cells where they have been found to underlie vascular function. The following studies first characterize the biophysical properties of TRPV4 and TRPA1 sparklets in endothelial cells. TRPA1 channels are present in the endothelium of cerebral arteries and absent from other vascular beds, suggesting a critical, yet previously unknown function for the channel in this tissue. Research here describes the physiological function of TRPA1 channels as sensors of oxidative membrane degradation in cerebral artery endothelial cells. Further, the involvement of TRPA1 channels in delaying the onset of hypertension-associated spontaneous hemorrhagic stroke is examined.